(untitled) (TEL Tempo, Espaço e Linguagem, 2024)
This article intends to present and historicize the literature and intellectual trajectory of Esmeralda Ribeiro. The writer and coordinator of Quilombhoje has authored dozens of short stories and poems, primarily - but not exclusively - published in the anthology Cadernos Negros, inaugurated in 1978. The aim is, therefore, to provide a broad overview of her publications and trajectory, as well as to explore the paths (intellectual and political) opened by her texts and activism. Moreover, this research engages with Esmeralda in envisioning the encruzilhada as a political and epistemological concept for mobilizing knowledge, a point of departure for contemplating the intersections between gender, race, class, sexuality, etc., in research and the poetics/politics of everyday life. Keywords: Literature. Gender. Race. Esmeralda Ribeiro. Black Notebooks